Serpentirhabdias mexicanus n. sp. (Nematoda: Rhabdiasidae), a parasitic lungworm of the nauyaca viper Bothrops asper (Serpentes: Viperidae) in the Mexican Neotropics - Velázquez-Brito, Andrés; García-Prieto, Luis; Garduño-Montes de Oca, Uriel; Sosa-Jiménez, Víctor Manuel; Vera-Chávez, Mirna Crizel; León-Règagnon, Virginia (Systematic parasitology, 2024)
Serpentirhabdias mexicanus n. sp. (Nematoda: Rhabdiasidae) is described from the lung of the nauyaca viper Bothrops asper in Puebla State, central Mexico. This new species is the fifth of the genus described having onchia. Among the species included in this group, the new species is morphologically closest to S. viperidicus and S. atroxi . However, it differs from both species mainly by having only one excretory gland (compared to two present in S . viperidicus and S . atroxi ). In addition, S. mexicanus n. sp. can be separated of S . viperidicus by tail length, shape of vulval lips, geographic distribution and host species and from S. atroxi by body length, number of papillae in the cephalic region, as well as the host species and geographic distribution. In the present study, we propose the new species based on morphological, host spectrum and genetic evidence. Phylogenetic analysis indicated Serpentirhabdias as a monophyletic group, with two subgroups that are congruent with the presence/absence of onchia in the esophagostome, host association and other relevant morphological characters.